Epidemiology and spectrum of vibrio diarrheas in the lower cross river basin of Nigeria - Eko, F O; Udo, S M; Antia-Obong, O E (Central European journal of public health, 1994)
In 1991 a cholera epidemic occurred in Nigeria. The features of this cholera outbreak in a single hospital in Cross River, Nigeria, were examined. Microbiologic techniques included the use of thiosulphate citrate bile-salts sucrose (TCBS) medium for culture of all stool specimens. Vibrio isolates from diarrheic patients included V. cholerae-O1 (75), V. cholerae non-O1 (10) and V. parahaemolyticus (21). The illnesses were diverse, ranging from mild to severe, and in most instances requiring hospitalization, rehydration as well as antibiotic treatment. Eighty patients were hospitalized and six died mainly from hypovolemic shock and acute renal failure arising from excessive fluid loss. The low vibrio-associated mortality observed in this outbreak may have been influenced by the proximity and easy transit access to the health care facilities offered by the teaching hospital. This contrasts with the high mortality figures reported by Health Centers in the rural areas during the same period. Some features of vibrio diarrheas were comparable with those of other enteric pathogens. Poorly developed water and sewage disposal systems, contact with sea water, consumption of fishery products and leftover foods were the main risk factors identified.
Keywords: Microbiological Techniques; dítě; Vibrio parahaemolyticus; Aged; Adolescent; mikrobiologické techniky; lidé středního věku; senioři; potravinářská mikrobiologie; předškolní dítě; Vibrio cholerae; Nigeria; lidé; Risk Factors; Adult; Middle Aged; dospělí; Gastroenteritis; kojenec; Female; gastroenteritida; těhotenství; Nigérie; průjem; Male; ženské pohlaví; sanitace; Child; Cholera; epidemický výskyt choroby; mužské pohlaví; Humans; Disease Outbreaks; Diarrhea; Sanitation; Pregnancy; rizikové faktory; Food Microbiology; Infant; Child, Preschool; cholera; mladiství